Pembinaan Public Speaking di Desa Samaturue - Wardayanti; Suriyati; Irmayanti; Muh. Judrah; Mustamir (KHIDMAH: Jurnal Pengabdian Masyarakat, 2023)
Messaging technique or public speaking is a skill that is always the center of attention. Scientifically, public speaking is included in the category of communication science which is absolute. Public speaking ability must be owned by an educator. A public speaker is required to be able to influence or convince his listeners through the words that come out of his mouth. For this reason, practice is needed to hone everyone's speaking skills, bearing in mind that it is not only educators who need good and correct public speaking. The purpose of carrying out this activity is so that the educators and youth organizations in Samaturue Village are able to understand public speaking techniques or speak in public more confidently, are more confident in appearing and expressing opinions, besides that especially educators in Samaturue Village with This activity is expected to improve the quality of teaching and learning atmosphere. There are several stages, namely socialization, implementation and evaluation. It is also hoped that the results of the coaching that has been carried out will be carried out further in the future, seeing the enthusiasm and feedback from the community in Samaturue Village to the presenters in this activity.